Optimizing of Resources Utilization Through Islamic Spiritual Enterpreneurship to Improve The Welfare of Coastal Communities - Rustan Rustan; Andi Arifwangsa Adiningrat; Siti Aisyah (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to determine the efforts of coastal communities in optimizing the utilization of natural resources through Islamic Spiritual Entrepreneurship which is applied to improve the welfare of coastal communities. The urgency of research on the principle of "Islamic Spiritual Entrepreneurship" instilled in coastal communities is the belief that Allah is almighty and will provide broad sustenance and be blessed by Allah SWT. This research was conducted on coastal communities in Pantai Biru, Jalan Metro Tanjung Bunga, Tamalate District, Makassar City. Sampling was carried out randomly from coastal communities, which were then conducted direct interviews using a list of questions. The data obtained were then analyzed using a qualitative descriptive analysis. The results of the study show that Islamic Spiritual Entrepreneurship has an effect on optimizing the use of resources in coastal areas, so as to improve the welfare of coastal communities. Optimizing the use of resources through Islamic Spiritual Entrepreneurship can be a solution in improving the welfare of coastal communities. By applying Islamic principles and good business ethics, businesses can be run in a more sustainable manner and pay attention to social and environmental responsibilities